Mixed Photon and Carbon-Ion Beam Radiotherapy in the Management of Non-Metastatic Nasopharyngeal Carcinoma - Hu, Jiyi; Huang, Qingting; Gao, Jing; Hu, Weixu; Yang, Jing; Guan, Xiyin; Qiu, Xianxin; Zhang, Wenna; Kong, Lin; Lu, Jiade J. (Frontiers in Oncology, 2021)
Background: Carbon-ion radiotherapy (CIRT) may further increase the therapeutic ratio for patients with newly diagnosed nasopharyngeal carcinoma (NPC). The purpose of the current study is to examine the effectiveness and toxicity profile of photon-based intensity-modulated radiotherapy (IMRT) plus CIRT boost in a relatively large cohort of NPC patients. Methods: In the current study, non-metastatic NPC patients treated with IMRT plus CIRT boost at Shanghai Proton and Heavy Ion Center between 6/2015 and 6/2018 were included. Overall survival (OS), progression-free survival (PFS), local control, regional control and distant control were calculated with Kaplan-Meier method. Acute and late toxicities were graded using CTCAE 4.03. Results: A total of 69 patients were included in the analysis. Among those, 74% of the patients had locoregionally advanced (stage Ⅲ/Ⅳ) disease and 92.8% had cervical lymphadenopathy. With a median follow-up of 31.9 months, the 3-year OS, PFS, local control, regional control, and distant control rates were 94.9%, 85.2%, 96.9%, 98.4%, and 89.7%, respectively. Mixed treatment of IMRT with CIRT boost was well tolerated. Severe acute toxicities induced by radiation therapy were observed in only 2 patients (dermatitis). No severe radiation-induced late toxicity was observed at the time of analysis. Univariable analysis showed N2/3 disease were correlated with an inferior distant control (p=0.040). Conclusion: Mixed treatment of IMRT plus CIRT boos provides an excellent disease control and a favorable toxicity profile for patients with non-metastatic NPC. Further follow-up is necessary to evaluate the long-term survivals and toxicities more accurately.